Rancang Bangun 3 Phase Energy Meter Untuk Analisis Kualitas Daya Di Industri - Wahyudi, Sri; Prasetyono, Eka; Anggriawan, Dimas Okky; Yuliana, Mike; Budikarso, Anang (JURNAL INTEGRASI, 2023)
The quality of electric power is one of the most important things in the industrial world, with good power quality, industrial efficiency will also increase which will result in savings in production costs. Energy consumption must also be monitored in such a way for the purposes of analyzing electrical energy efficiency. Therefore, the author designed a tool called a 3 phase energy meter that can monitor energy consumption and power quality for industry with a 3 phase electrical system. The 3 phase energy meter is equipped with an IoT system so that the observation of the measurement results of every electrical machine system in the industry can be done at one point without having to go to the location. The hope is that with the 3 phase energy meter, it can improve production efficiency through power quality analysis.